2016
DOI: 10.4238/gmr.15018299
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress alters DNA methylation levels in alfalfa (Medicago spp)

Abstract: ABSTRACT. Modification of DNA methylation status is one of the mechanisms used by plants to adjust gene expression at both the transcriptional and posttranscriptional levels when plants are exposed to suboptimal conditions. Under abiotic stress, different cultivars often show heritable phenotypic variation accompanied by epigenetic polymorphisms at the DNA methylation level. This variation may provide the raw materials for plant breeding programs that aim to enhance abiotic stress tolerance, including salt tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…This is interesting that desiccation stress response in Nagina 22 is mediated via hypomethylation in CHH context and salinity stress response in Pokkali is mediated via hypermethylation in CHH context. Previous studies have also demonstrated that hypomethylation associated with higher gene expression under drought/salinity stress response and hypermethylation associated with higher gene expression under salinity stress response (Boyko et al ., 2010; Wang et al ., 2014; Al-Lawati et al ., 2016). These results suggest that abiotic stress response(s) is dependent on cultivar specific manner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is interesting that desiccation stress response in Nagina 22 is mediated via hypomethylation in CHH context and salinity stress response in Pokkali is mediated via hypermethylation in CHH context. Previous studies have also demonstrated that hypomethylation associated with higher gene expression under drought/salinity stress response and hypermethylation associated with higher gene expression under salinity stress response (Boyko et al ., 2010; Wang et al ., 2014; Al-Lawati et al ., 2016). These results suggest that abiotic stress response(s) is dependent on cultivar specific manner.…”
Section: Resultsmentioning
confidence: 99%
“…However, methylation differences between drought-tolerant and susceptible cultivars under control conditions were mostly found in CG context in rice (Garg et al ., 2015). Likewise, methylation dynamics under salinity stress have also been investigated in susceptible and tolerant cultivars in different plants using various approaches, and methylation changes under the stress conditions were found to be genotype-specific (Wang et al ., 2014; Al-Lawati et al ., 2016; Lu et al ., 2017). Interestingly, methylation changes induced in response to abiotic stress condition(s) reversed to its original methylation status after stress recovery (Wang et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This method is based primarily on Amplified Fragments Length Polymorphism (AFLP) analysis. 49 It uses two different reactions with MspI/EcoRI, and HpaII/EcoRI. The isoschizomeres recognize the same DNA site 5 0 -CCGG-3 0 with different sensitivity to methylation.…”
Section: Msap Epigenotypingmentioning
confidence: 99%
“…Overall, the emergence for the appreciation of the role of epigenetics in an ecological context has developed in both aquatic and terrestrial systems (Bonduriansky et al, 2012). Studies on plants have dominated the literature on ecological epigenetics (Schrey et al, 2013;Baulcombe and Dean, 2014;Verhoeven et al, 2016), especially in response to stress (Wang et al, 2011;Grativol et al, 2012;Al-Lawati et al, 2016). On the marine side, epigenetic and epigenomic approaches are being used to explore areas such as (1) sources of phenotypic plasticity, as created by differential gene expression (Dixon et al, 2014;Dimond and Roberts, 2016;Marsh et al, 2016), (2) mechanisms involved in development (Riviere et al, 2013), and (3) a possible rapid response to anthropogenic environmental change (Putnam et al, 2016).…”
Section: Epigenetics-a Brief Overviewmentioning
confidence: 99%